تعليم القواعد النحوية: بين المشاكل والحل - Khitam, Achmad Khusnul (Al Mah?ra: Jurnal Pendidikan Bahasa Arab, 2018)
As we know that the problem of teaching Arabic is still considered as one of the most fundamental issues, not only for those who speak Arabic, but also for the children of this language. As for grammar, it is the most educated and incomprehensible since it has many rules that relate to each other. Students with this difficulty have claimed that these hard rules can not be understood with the teacher's weakness in applying the good way to defend their jealousy. This research aims at searching for teaching grammatical rules and then completing it by mentioning some of the problems that students faced in learning and how to solve them with explaining the truth of education first and the grammar with a brief explanation. It is understood from this research that students face many problems in learning the Arabic language, including the abundance of language laws, the many different aspects of Circumcision, the multiplicity of mixed mabahith, and others. The solution that students and teachers can use is a lot of training, purification and simplification of grammar, and so on. Keywords: teaching, grammar, problems, solution.